Developing Middle School Students' Interests in STEM via Summer Learning Experiences: See Blue STEM Camp. (October 2014) - Mohr‐Schroeder, Margaret J.; Jackson, Christa; Miller, Maranda; Walcott, Bruce; Little, David L.; Speler, Lydia; Schooler, William; Schroeder, D. Craig
<x xml:space="preserve">Abstract</x> It is a well‐known fact that, in general, many students have a lack of interest and proficiency in mathematics and science. Therefore, it is imperative that we prepare and inspire all students, specifically students of underrepresented populations, to learn science, technology, engineering, and mathematics (STEM) content. Now in its fourth year, See Blue STEM Camp was created in order to expose middle‐level students to a variety of STEM fields and STEM professionals through hands‐on project‐based learning experiences in order to increase their interest in STEM. This paper describes the structure and the activities of the camp. In this innovative project, we utilized an embedded mixed methods study design to investigate the extent middle level students' attitudes, perceptions, and interest in and toward STEM fields and careers changed after participating in an informal learning environment of a five‐day day camp held on the campus of a major university in the mid‐south. The results revealed an increase in their motivation and interest in STEM fields; in fact, there was 3% increase from pre to post in interest in STEM careers. The data also revealed that a majority of the participating middle school students found the STEM content sessions "fun" and engaging, specifically citing the hands‐on experiences they received.